The effect of auditor's competency and independence on audit quality of the internal supervision of Halu Oleo University - Erwin Hadisantoso; Arifuddin Mas’ud; Elfa Aulia Aqilah (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
The purpose of this study was to determine the effect of auditor competence and independence on the audit quality of the Halu Oleo University Internal Supervisory Unit. The sample in this study was 51 audites. The data used in this study are qualitative data and quantitative data. Data collection methods are questionnaires and documentation. Methods Data analysis used descriptive analysis and multiple linear regression analysis. The results of the analysis show an R value of 0.859 which means that the correlation between the independent variables of competence and independence on audit quality at the internal supervisory unit of Halu Oleo University is strong because the value is above 0.75. Furthermore, the value of R2 (R-Square) is 0.800. This means that the diversity of auditor competence and auditor independence variables on audit quality can be explained by the model by 80% and the remaining 20% is explained by other variables outside this research model, so that this research model has a good accuracy or accuracy model. Simultaneous test results obtained a significance value of F or probability of 0.000 <0.05 at the 95% confidence level. These results indicate that both auditor competence and auditor independence variables simultaneously have a positive and significant effect on audit quality at the internal supervisory unit of Halu Oleo University. The results of this study can also prove from the standardized coefficient value and t-value that the independence variable has a greater value than the auditor's competence. This means that auditor independence is the dominant variable in influencing audit quality compared to the competence of auditors in the internal supervisory unit of Halu Oleo University.